Are women more susceptible than men to drug‐induced QT prolongation? Concentration–QTc modelling in a phase 1 study with oral rac‐sotalol. (March 2014) - Darpo, Borje; Karnad, Dilip R.; Badilini, Fabio; Florian, Jeff; Garnett, Christine E; Kothari, Snehal; Panicker, Gopi Krishna; Sarapa, Nenad
<x xml:space="preserve">Abstract</x> Aim To study the differences in QTc interval on ECG in response to a single oral dose of rac‐sotalol in men and women. Methods Continuous 12‐lead ECGs were recorded in 28 men and 11 women on a separate baseline day and following a single oral dose of 160 mg rac‐sotalol on the following day. ECGs were extracted at prespecified time points and upsampled to 1000 Hz and analyzed manually in a central ECG laboratory on the superimposed median beat. Concentration–QTc analyses were performed using a linear mixed effects model. Results Rac‐sotalol produced a significant reduction in heart rate in men and in women. An individual correction method (QTcI) most effectively removed the heart rate dependency of the QTc interval. Mean QTcI was 10 to 15 ms longer in women at all time points on the baseline day. Rac‐sotalol significantly prolonged QTcI in both genders. The largest mean change in QTcI (ΔQTcI) was greater in females (68 ms (95% confidence interval (CI) 59, 76 ms) vs. 27 ms (95% CI 22, 32 ms) in males). Peak rac‐sotalol plasma concentration was higher in women than in men (mean Cmax 1.8 μg ml−1 (range 1.1–2.8) vs. 1.4 μg ml−1 (range 0.9–1.9), P = 0.0009). The slope of the concentration–ΔQTcI relationship was steeper in women (30 ms per μg ml−1vs. 23 ms per μg ml−1 in men; P = 0.0135). Conclusions The study provides evidence for a greater intrinsic sensitivity to rac‐sotalol in women than in men for drug‐induced delay in cardiac repolarization.